2016
DOI: 10.1021/acs.bioconjchem.6b00494
|View full text |Cite
|
Sign up to set email alerts
|

Surface Ligand Density of Antibiotic-Nanoparticle Conjugates Enhances Target Avidity and Membrane Permeabilization of Vancomycin-Resistant Bacteria

Abstract: Many bacterial pathogens have now acquired resistance toward commonly used antibiotics, such as the glycopeptide antibiotic vancomycin. In this study, we show that immobilization of vancomycin onto a nanometer-scale solid surface with controlled local density can potentiate antibiotic action and increase target affinity of the drug. Magnetic nanoparticles were conjugated with vancomycin and used as a model system to investigate the relationship between surface density and drug potency. We showed remarkable imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 42 publications
1
33
0
Order By: Relevance
“…In a recent study, Hassan et al reported that the conjugation of vancomycin ( 34 ) with magnetic NPs significantly increased antimicrobial activity against vancomycin‐resistant bacteria, including S. aureus , E. faecium , and Enterococcus faecalis. The biological results demonstrated that the magnetic‐NP‐conjugated vancomycin ( 106 ) exhibited much smaller MICs against vancomycin‐resistant strains when compared to the free glycopeptide antibiotic ( 34 ) (MICs of 13‐28 and 250‐4000 µg/mL, respectively) . In addition, higher surface densities resulted in an enhanced affinity towards bacteria, with ( 106 ) causing rapid permeabilization through the bacterial cell wall within 2 hours, whereas no effect was observed with free vancomycin.…”
Section: Other Antimicrobial‐carrier Conjugatesmentioning
confidence: 99%
See 3 more Smart Citations
“…In a recent study, Hassan et al reported that the conjugation of vancomycin ( 34 ) with magnetic NPs significantly increased antimicrobial activity against vancomycin‐resistant bacteria, including S. aureus , E. faecium , and Enterococcus faecalis. The biological results demonstrated that the magnetic‐NP‐conjugated vancomycin ( 106 ) exhibited much smaller MICs against vancomycin‐resistant strains when compared to the free glycopeptide antibiotic ( 34 ) (MICs of 13‐28 and 250‐4000 µg/mL, respectively) . In addition, higher surface densities resulted in an enhanced affinity towards bacteria, with ( 106 ) causing rapid permeabilization through the bacterial cell wall within 2 hours, whereas no effect was observed with free vancomycin.…”
Section: Other Antimicrobial‐carrier Conjugatesmentioning
confidence: 99%
“…In addition, higher surface densities resulted in an enhanced affinity towards bacteria, with ( 106 ) causing rapid permeabilization through the bacterial cell wall within 2 hours, whereas no effect was observed with free vancomycin. The authors suggested that the immobilization of conventional antibiotics onto a nanometer‐scale solid surface with a controlled local density may re‐potentiate the action and increase the target affinity of the anti‐infective agents, which are currently clinically failing due to their toxicity or the resistance of micro‐organisms …”
Section: Other Antimicrobial‐carrier Conjugatesmentioning
confidence: 99%
See 2 more Smart Citations
“…Importantly, Brown’s study showed that both nanoparticulate formulations exhibited unique properties, which avoided the mechanisms deployed by bacteria that commonly result in the rise of multidrug resistance [ 79 ]. Hassan and colleagues reported the use of vancomycin-coated magnetic nanoparticles as anti-bacterial agents [ 80 ]. The novel formulation was tested against vancomycin resistant strains, exhibiting minimum inhibitory concentrations as low as 13–28 µg·mL −1 compared with 250–4000 µg·mL −1 for the free drug.…”
Section: Nanoparticles As Anti-microbial Agentsmentioning
confidence: 99%